2020
DOI: 10.3390/coatings10040422
|View full text |Cite
|
Sign up to set email alerts
|

The Trends of TiZr Alloy Research as a Viable Alternative for Ti and Ti16 Zr Roxolid Dental Implants

Abstract: Despite many discussions about Ti versus Zr, Ti remains the golden standard for dental implants. With the extended use of implants, their rejection in peri-implantitis due to material properties is going to be an important part of oral health problems. Extended use of implants leading to a statistical increase in implant rejection associated with peri-implantitis raises concerns in selecting better implant materials. In this context, starting in the last decade, investigation and use of TiZr alloys as alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…Although higher hydrophilic surfaces were reported to be better for interacting with biological fluids, cells, and tissues 27) , our results showed the opposite trend that the attached cell density was smaller on the surface of higher hydrophilic Ti-50Zr than on lower hydrophilic c.p.Ti, Ti-10Zr, and Ti-30Zr. It was found that higher hydrophilicity and larger roughness may attract more tissue fluid to increase osteogenic cell migration onto materials 28) . However, less cell attachment on Ti-50Zr suggested that the impact of roughness outweighed that of hydrophilicity because Ti-50Zr alloy exhibited higher hydrophilicity but lower roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher hydrophilic surfaces were reported to be better for interacting with biological fluids, cells, and tissues 27) , our results showed the opposite trend that the attached cell density was smaller on the surface of higher hydrophilic Ti-50Zr than on lower hydrophilic c.p.Ti, Ti-10Zr, and Ti-30Zr. It was found that higher hydrophilicity and larger roughness may attract more tissue fluid to increase osteogenic cell migration onto materials 28) . However, less cell attachment on Ti-50Zr suggested that the impact of roughness outweighed that of hydrophilicity because Ti-50Zr alloy exhibited higher hydrophilicity but lower roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 90 ] used induction heating combined with alkali treatment to prepare a stable layered micro-nanoporous network structure on the surface of Ti, resulting in a more uniform coating surface with a higher number of pores, and improved roughness, wettability, and bonding strength with the matrix, as well as significantly improved in vitro and in vivo biocompatibility properties. Manole et al [ 91 , 92 ] deposited n-type semiconducting TiO 2 nanowires onto a Ti-50Zr surface by electrostatic spinning and improved the hydrophilic and corrosion behavior of the alloy surface whilst avoiding significant inflammatory processes. The protection efficiency of the coatings remained greater than 51%.…”
Section: Surface Modification For Biomedical Ti and Ti Alloysmentioning
confidence: 99%
“…There are several alloys with low density, resistance to corrosion, and reduced ion release in a large number of environments, as well as good mechanical behavior for a large temperature domain. These properties recommend alloys such as stainless steel, CoCr, aluminum, magnesium, and titanium alloys, also depending on other factors, namely, thermal and electrical properties, wear, stability, and processing costs, to be used in various industrial applications and the medical field [43][44][45][46][47][48].…”
Section: Trends In Enhancing Coatings Performances On Cocr Alloys and Other Metallic Alloys (Including High-entropy Alloys)mentioning
confidence: 99%